DISTRIBUSI MASSA OTOT DAN LEMAK VISCERAL PADA ATLET WANITA AKUATIK: IMPLIKASI TERHADAP PERFORMA DAN KESEHATAN - Sugiarto, Dinta; Ghozali, Dhoni Akbar; Mukti, Ibrah Fastabiqi Bawana; Bakti, Ananda Perwira (Journal of Physical Activity and Sports (JPAS), 2025)
Good physical performance must also prioritize metabolic health. Metabolic health is influenced by body composition, including muscle mass and visceral fat. Muscle mass plays a role in the performance and quality of body metabolism, while visceral fat around the liver, pancreas, and intestines is an indicator of metabolic health that affects insulin resistance, chronic inflammation, and metabolic diseases. Good training is needed to find the right recipe for maximizing muscle mass and controlling visceral fat levels. This study aims to compare muscle mass and visceral fat in female aquatic athletes to see health parameters without neglecting performance. This study used a cross-sectional design involving 15 subjects from female swimming and diving athletes from the KONI Malang City pool. Measurement of muscle mass and visceral fat used a BIA (Bioelectrical Impedance Analysis) tool. Correlation analysis was used to determine the relationship between muscle mass and visceral fat. The results showed that all research subjects had low muscle mass with a maximum value of 21.03 and visceral fat in the high category of 0.67. Low muscle mass is likely caused by suboptimal training outcomes or by strength training not maximizing muscle mass composition, while high visceral fat can be influenced by poor nutritional management by athletes. Physical performance and metabolic health are crucial, especially in optimizing muscle mass and minimizing visceral fat. Low muscle mass is caused by inadequate training methods, particularly strength training, including a lack of attention to training principles such as intensity, frequency, and loading.